Two-component sealant composition with low water vapor transmittance and preparation method thereof

By adopting a two-component sealant composition with low water vapor transmission, the problems of complex sealing process, high cost and low efficiency of photovoltaic modules are solved, and the effects of reducing water vapor transmission, improving bonding strength and mechanical properties are achieved, and the luminous efficiency and production efficiency of photovoltaic modules are improved.

CN119592296APending Publication Date: 2025-03-11DONG GUAN CITY JIA DI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411954211.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The sealant of existing photovoltaic modules has complex processes, high cost and low efficiency, and the high water vapor transmittance affects the luminous efficiency.

Method used

A two-component sealant composition with low water vapor transmittance, including components A and components B, is used to reduce the water vapor transmittance of the silicone sealant and improve the bonding strength and mechanical properties through specific raw material ratios and preparation methods.

Benefits of technology

It effectively reduces the water vapor transmission rate of silicone sealant, improves the luminous efficiency of photovoltaic modules due to the influence of water vapor transmission, reduces the sealing construction process, reduces costs and improves efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention particularly relates to a low-water-vapor-transmittance two-component sealant composition and a preparation method thereof.The low-water-vapor-transmittance two-component sealant composition comprises a component A and a component B, the component A is prepared from the following raw materials in parts by weight: 30 to 50 parts of alkoxy terminated polydimethylsiloxane, 40 to 70 parts of nano calcium carbonate, 0.5 to 1 part of vinyl trimethoxy silane, 1 to 4 parts of methyl trimethoxy silane, 0.5 to 1 part of diamino silane oligomer and 0.02 to 0.08 part of organic tin chelate; the component B is prepared from the following raw materials in parts by weight: 10 to 20 parts of silane-terminated polyether polymer, 20 to 50 parts of nano calcium carbonate, 2 to 10 parts of maleic anhydride polyisobutene, 5 to 15 parts of polyisobutene, 1 to 5 parts of butyl rubber and 0.3 to 0.5 part of vinyl trimethoxy silane. The two-component sealant composition has low water vapor transmission rate and good bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a two-component sealant composition with low water vapor transmission rate and a preparation method thereof. Background Art

[0002] In the prior art, in order to stabilize the power generation efficiency, photovoltaic modules often need edge sealing to isolate moisture. The current solution is to seal the inner layer with butyl tape and the outer layer with condensation-type silicone sealant to achieve a good sealing effect. However, the current process often has the following problems: butyl glue is a hot-melt butyl glue, which needs to be heated to 130-180°C during construction. After construction, butyl glue is a weak adhesive tape that is easy to peel off. A layer of silicone sealant is also required on the outer layer to fix the seal. This solution has defects such as complex process, high cost and low efficiency, which affects the development of the industry. The Chinese invention patent with publication number CN 101735745A discloses a solar photovoltaic module sealant and its synthesis method, in which polyisobutylene and butyl rubber are selected as polymers, and the shear force is low, which is 25 PSI (0.17MPa), while the shear strength required by photovoltaic modules is generally about 1-2MPa, and the market price of butyl glue is high, about 5-10 times that of silicone sealant, which is not the preferred solution in terms of performance and cost. A Chinese invention patent with publication number CN 113337245 A discloses an alcohol-based photovoltaic module sealant and a preparation method thereof. This method enhances the adhesiveness and deep curing properties of traditional sealants, but fails to solve the problem of low water vapor transmission rate of photovoltaics. Summary of the invention

[0003] The purpose of the present invention is to solve the above-mentioned deficiencies of the prior art and provide a two-component sealant composition with low water vapor transmission rate and a preparation method thereof, wherein the two-component sealant composition can effectively reduce the water vapor transmission rate of the silicone sealant and improve the problem that the luminous efficiency of the photovoltaic module is affected by water vapor transmission. The preparation method of the two-component sealant composition has a simple process, is easy to control, has low production cost, high production efficiency, and is conducive to industrial production.

[0004] The object of the present invention is achieved by the following technical scheme: a two-component sealant composition with low water vapor transmission rate, comprising component A and component B, wherein component A comprises the following raw materials in parts by weight: 30-50 parts of alkoxy-terminated polydimethylsiloxane, 40-70 parts of nano-calcium carbonate, 0.5-1 parts of vinyl trimethoxy silane, 1-4 parts of methyl trimethoxy silane, 0.5-1 parts of bisamino silane oligomer, and 0.02-0.08 parts of organic tin chelate; and component B comprises the following raw materials in parts by weight: 10-20 parts of silane-terminated polyether polymer, 20-50 parts of nano-calcium carbonate, 2-10 parts of maleic anhydride polyisobutylene, 5-15 parts of polyisobutylene, 1-5 parts of butyl rubber, and 0.3-0.5 parts of vinyl trimethoxy silane.

[0005] The sealant composition of the present invention adopts a two-component form, wherein alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer, and organic tin chelate are matched to prepare component A, and silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber, and vinyl trimethoxysilane are matched to prepare component B. When used, component A and component B are mixed, which can effectively avoid the separation of butyl rubber, polyisobutylene, etc. in the uncured organic silicon system due to long-term storage. Compared with ordinary organic silicon sealant, the two-component sealant composition can effectively reduce the water vapor permeability of organic silicon sealant, improve the luminous efficiency of photovoltaic modules affected by water vapor permeation, and has good bonding strength and mechanical properties. When applied to photovoltaic modules, it can reduce the sealing construction process of photovoltaic modules, reduce costs, and improve efficiency.

[0006] Furthermore, the alkoxy-terminated polydimethylsiloxane is at least one of trimethoxy-terminated polydimethylsiloxane and vinyl dimethoxy-terminated polydimethylsiloxane.

[0007] Furthermore, the organic tin chelate is at least one of chelated tin U-220H, chelated tin U-303 and KRA-1.

[0008] Furthermore, the preparation method of the silane-terminated polyether polymer comprises the following steps: (S1) under the protection of nitrogen atmosphere, polyoxypropylene glycol and polytetrahydrofuran diol are added into a container, heated to 90-100° C., 3-isocyanate propyltriethoxysilane and a catalyst are added dropwise while stirring, and reacted for 4-7 hours to obtain a mixture 1; (S2) Add white carbon black to the mixture, stir at 80-90°C for 3-5h, degas under reduced pressure at a vacuum degree of -0.08~-0.09Mpa, and filter to obtain a filtrate to obtain a silane-terminated polyether polymer.

[0009] Furthermore, in step (S1), the catalyst is at least one of stannous octoate, dibutyltin dilaurate and dibutyltin diacetate.

[0010] Furthermore, in step (S1), the molecular weight of the polyoxypropylene glycol is 6000-14000. The molecular weight of the polytetrahydrofuran diol is 2000-4000. The present invention can effectively adjust the viscosity and crosslinking density of the silane-terminated polyether polymer by using the polyoxypropylene glycol and polytetrahydrofuran diol with the above molecular weights, which helps to improve the mechanical properties of the sealant composition.

[0011] Furthermore, in step (S1), the mass ratio of polyoxypropylene glycol to polytetrahydrofuran diol is 2-4:1, the addition ratio of polyoxypropylene glycol, polytetrahydrofuran diol and 3-isocyanate propyl triethoxy silane is such that the molar ratio of hydroxyl group to isocyanate group is 1:0.9-1.1; and the addition amount of the catalyst is 0.1-0.3% of the sum of the mass of polyoxypropylene glycol and 3-isocyanate propyl triethoxy silane.

[0012] Furthermore, in step (S2), the amount of white carbon black added is 1.5-4% by mass of the mixture.

[0013] The present invention uses the above raw materials and preparation method to prepare a silane-terminated polyether polymer, and the silane-terminated polyether polymer is added to a sealant composition to help improve the mechanical properties and bonding properties of the sealant composition. The white carbon black of the present invention can effectively absorb the catalyst residue in the silane-terminated polyether polymer, improve the storage stability of the silane-terminated polyether polymer, and make the silane-terminated polyether polymer have good mechanical properties.

[0014] Furthermore, in the components A and B, the particle size of the nano calcium carbonate is 30-80 nm.

[0015] The present invention also provides a method for preparing the above-mentioned two-component sealant composition with low water vapor transmission rate, comprising the following steps: (1) taking alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate in proportion, stirring and mixing them evenly under vacuum conditions to obtain component A; (2) taking silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane in proportion, stirring and mixing them evenly under vacuum conditions to obtain component B; (3) When in use, component A and component B are mixed in proportion to obtain a two-component sealant composition.

[0016] Furthermore, in step (1), alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate are added to a vacuum planetary mixer in proportion, and stirred for 60-120 minutes at a vacuum degree of -0.08 to -0.09 MPa and a rotation speed of 800-1200 rpm to obtain component A.

[0017] Furthermore, in step (2), silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane are added to a vacuum planetary mixer in proportion, and stirred for 60-120 minutes at a vacuum degree of -0.08 to -0.09 MPa and a rotation speed of 800-1200 rpm to obtain component B.

[0018] Furthermore, the mass ratio of component A to component B is 1:0.8-1.2.

[0019] The beneficial effects of the present invention are as follows: compared with ordinary silicone sealants, the low water vapor permeability two-component sealant composition of the present invention can effectively reduce the water vapor permeability of silicone sealants, improve the luminous efficiency of photovoltaic modules affected by water vapor permeation, and has good bonding strength and mechanical properties. The sealant composition of the present invention adopts a two-component form, which effectively avoids the separation of butyl rubber, polyisobutylene, etc. in the uncured silicone system due to long-term storage. When the two-component sealant composition of the present invention is applied to photovoltaic modules, it can reduce the sealing construction process of photovoltaic modules, reduce costs, and improve efficiency. The preparation method of the two-component sealant composition is simple in process, easy to control, low in production cost, high in production efficiency, and is conducive to industrial production. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0021] In some embodiments of the present invention, a two-component sealant composition with low water vapor transmission rate includes component A and component B, wherein component A includes the following raw materials in parts by weight: 30-50 parts of alkoxy-terminated polydimethylsiloxane, 40-70 parts of nano-calcium carbonate, 0.5-1 parts of vinyltrimethoxysilane, 1-4 parts of methyltrimethoxysilane, 0.5-1 parts of bisaminosilane oligomer, and 0.02-0.08 parts of organic tin chelate; The component B comprises the following raw materials in parts by weight: 10-20 parts of silane-terminated polyether polymer, 20-50 parts of nano calcium carbonate, 2-10 parts of maleic anhydride polyisobutylene, 5-15 parts of polyisobutylene, 1-5 parts of butyl rubber, and 0.3-0.5 parts of vinyl trimethoxy silane.

[0022] In some embodiments of the present invention, the alkoxy-terminated polydimethylsiloxane is at least one of trimethoxy-terminated polydimethylsiloxane and vinyl dimethoxy-terminated polydimethylsiloxane.

[0023] In some embodiments of the present invention, the organic tin chelate is at least one of chelated tin U-220H, chelated tin U-303 and KRA-1.

[0024] In some embodiments of the present invention, the molecular weight of the polyisobutylene is 400-2400. The polyisobutylene is moisture-cured polyisobutylene, and the polyisobutylene of Hangzhou Henkel New Materials SIPIB1300 is used. In this embodiment, the moisture-cured polyisobutylene is used to increase the anchoring performance and physical strength of the polyisobutylene in the colloid.

[0025] In some embodiments of the present invention, the method for preparing the silane-terminated polyether polymer comprises the following steps: (S1) under the protection of nitrogen atmosphere, adding polyoxypropylene glycol and polytetrahydrofuran diol into a container, heating to 90-100° C., adding 3-isocyanate propyl triethoxysilane and a catalyst dropwise while stirring, reacting for 4-7 hours, and obtaining a mixture 1; the polyoxypropylene glycol is previously dehydrated and degassed under vacuum conditions; (S2) Add white carbon black to the mixture, stir at 80-90°C for 3-5h, degas under reduced pressure at a vacuum degree of -0.08~-0.09Mpa, and filter to obtain a filtrate to obtain a silane-terminated polyether polymer.

[0026] In some embodiments of the present invention, in step (S1), the catalyst is at least one of stannous octoate, dibutyltin dilaurate and dibutyltin diacetate.

[0027] In some embodiments of the present invention, in step (S1), the molecular weight of the polyoxypropylene glycol is 6000-14000. The molecular weight of the polytetrahydrofuran diol is 2000-4000.

[0028] In some embodiments of the present invention, in step (S1), in step (S1), the mass ratio of polyoxypropylene glycol and polytetrahydrofuran diol is 2-4:1, the addition ratio of polyoxypropylene glycol, polytetrahydrofuran diol and 3-isocyanate propyl triethoxy silane is such that the molar ratio of hydroxyl group to isocyanate group is 1:0.9-1.1; and the amount of the catalyst added is 0.1-0.3% of the sum of the masses of polyoxypropylene glycol and 3-isocyanate propyl triethoxy silane.

[0029] In some embodiments of the present invention, in step (S2), the amount of white carbon black added is 1.5-4% by mass of the mixture.

[0030] In some embodiments of the present invention, in the component A and the component B, the particle size of the nano calcium carbonate is 30-80 nm.

[0031] In an embodiment of the present invention, a method for preparing a two-component sealant composition with low water vapor transmission rate comprises the following steps: (1) taking alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate in proportion, stirring and mixing them evenly under vacuum conditions to obtain component A; (2) taking silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane in proportion, stirring and mixing them evenly under vacuum conditions to obtain component B; (3) When in use, component A and component B are mixed in proportion to obtain a two-component sealant composition.

[0032] In some embodiments of the present invention, in step (1), alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate are added to a vacuum planetary mixer in proportion, and stirred for 60-120 minutes at a vacuum degree of -0.08 to -0.09 Mpa and a rotation speed of 800-1200 rpm to obtain component A.

[0033] In some embodiments of the present invention, in step (2), silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane are added to a vacuum planetary mixer in proportion, and stirred for 60-120 minutes at a vacuum degree of -0.08 to -0.09 Mpa and a rotation speed of 800-1200 rpm to obtain component B.

[0034] In some embodiments of the present invention, the mass ratio of component A to component B is 1:0.8-1.2.

[0035] Example 1 The present embodiment provides a two-component sealant composition with low water vapor transmission rate, comprising component A and component B, wherein component A comprises the following raw materials in parts by weight: 40 parts of alkoxy-terminated polydimethylsiloxane, 55 parts of nano-calcium carbonate, 0.8 parts of vinyltrimethoxysilane, 2 parts of methyltrimethoxysilane, 0.8 parts of bisaminosilane oligomer, and 0.05 parts of organic tin chelate; and component B comprises the following raw materials in parts by weight: 15 parts of silane-terminated polyether polymer, 35 parts of nano-calcium carbonate, 8 parts of maleic anhydride polyisobutylene, 8 parts of polyisobutylene, 2 parts of butyl rubber, and 0.4 parts of vinyltrimethoxysilane.

[0036] In this embodiment, the butyl rubber is Yanshan Petrochemical Butyl Rubber 1751. The maleic anhydride polyisobutylene is Kuraray ISOBAM06 isobutylene maleic anhydride copolymer. The bisaminosilane oligomer is Evonik Dynasylan® 1146 bisaminosilane oligomer. The polyisobutylene is SIPIB1300 polyisobutylene from Hangzhou Henkel New Materials Co., Ltd.

[0037] Furthermore, the alkoxy-terminated polydimethylsiloxane is trimethoxy-terminated polydimethylsiloxane. The trimethoxy-terminated polydimethylsiloxane is RH-FD1500 purchased from Zhejiang Runhe Silicone Company.

[0038] Furthermore, the organic tin chelate is chelated tin U-220H.

[0039] Furthermore, the preparation method of the silane-terminated polyether polymer comprises the following steps: (S1) under the protection of nitrogen atmosphere, polyoxypropylene glycol is added into a container, heated to 95° C., 3-isocyanatepropyltriethoxysilane and a catalyst are added dropwise while stirring, and reacted for 6 hours to obtain a mixture 1; (S2) Add white carbon black to the mixture, stir at 85° C. for 4 h, degas under reduced pressure at a vacuum degree of -0.09 MPa, and filter to obtain a filtrate to obtain a silane-terminated polyether polymer.

[0040] Furthermore, in step (S1), the catalyst is stannous octoate, the molecular weight of the polyoxypropylene glycol is 8000, and the molecular weight of the polytetrahydrofuran diol is 2000.

[0041] Furthermore, in step (S1), in step (S1), the mass ratio of polyoxypropylene glycol and polytetrahydrofuran diol is 3:1, the addition ratio of polyoxypropylene glycol, polytetrahydrofuran diol and 3-isocyanate propyl triethoxy silane is a molar ratio of hydroxyl group to isocyanate group of 1:1; the amount of the catalyst added is 0.15% of the sum of the masses of polyoxypropylene glycol and 3-isocyanate propyl triethoxy silane.

[0042] Furthermore, in step (S2), the amount of white carbon black added is 2% of the mass of the mixture. The specific surface area of ​​the white carbon black is 200-300 m² / g.

[0043] Furthermore, in the components A and B, the particle size of the nano calcium carbonate is 30-80 nm.

[0044] This embodiment also provides a method for preparing the above-mentioned two-component sealant composition with low water vapor transmission rate, comprising the following steps: (1) taking alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate in proportion, stirring and mixing them evenly under vacuum conditions to obtain component A; (2) taking silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane in proportion, stirring and mixing them evenly under vacuum conditions to obtain component B; (3) When in use, component A and component B are mixed in a mass ratio of 1:1 to obtain a two-component sealant composition.

[0045] Furthermore, in step (1), alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate are added to a vacuum planetary mixer in proportion, and stirred for 90 minutes at a vacuum degree of -0.09 MPa and a rotation speed of 1000 rpm to obtain component A.

[0046] Furthermore, in step (2), silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane are added to a vacuum planetary mixer in proportion, and stirred for 90 minutes at a vacuum degree of -0.09 MPa and a rotation speed of 1000 rpm to obtain component B.

[0047] Example 2 The present embodiment provides a two-component sealant composition with low water vapor transmission rate, comprising component A and component B, wherein component A comprises the following raw materials in parts by weight: 40 parts of alkoxy-terminated polydimethylsiloxane, 55 parts of nano-calcium carbonate, 0.5 parts of vinyltrimethoxysilane, 2.6 parts of methyltrimethoxysilane, 0.5 parts of bisaminosilane oligomer, and 0.08 parts of organic tin chelate; and component B comprises the following raw materials in parts by weight: 15 parts of silane-terminated polyether polymer, 35 parts of nano-calcium carbonate, 5 parts of maleic anhydride polyisobutylene, 11 parts of polyisobutylene, 2 parts of butyl rubber, and 0.3 parts of vinyltrimethoxysilane.

[0048] Furthermore, the organic tin chelate is chelated tin KRA-1.

[0049] Furthermore, the preparation method of the silane-terminated polyether polymer comprises the following steps: (S1) under the protection of nitrogen atmosphere, polyoxypropylene glycol is added into a container, heated to 100° C., 3-isocyanatepropyltriethoxysilane and a catalyst are added dropwise while stirring, and reacted for 5 hours to obtain a mixture 1; (S2) Add white carbon black to the mixture, stir at 90°C for 4.5 hours, degas under reduced pressure at a vacuum degree of -0.09 MPa, and filter to obtain a filtrate to obtain a silane-terminated polyether polymer.

[0050] Furthermore, in step (S1), the catalyst is stannous octoate.

[0051] Furthermore, in step (S2), the amount of white carbon black added is 1.5% by mass of the mixture.

[0052] Furthermore, in the components A and B, the particle size of the nano calcium carbonate is 30-80 nm.

[0053] This embodiment also provides a method for preparing the above-mentioned two-component sealant composition with low water vapor transmission rate, comprising the following steps: (1) taking alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate in proportion, stirring and mixing them evenly under vacuum conditions to obtain component A; (2) taking silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane in proportion, stirring and mixing them evenly under vacuum conditions to obtain component B; (3) When in use, component A and component B are mixed in a mass ratio of 1:1 to obtain a two-component sealant composition.

[0054] Furthermore, in step (1), alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate are added to a vacuum planetary mixer in proportion, and stirred for 80 minutes at a vacuum degree of -0.09 Mpa and a rotation speed of 1200 rpm to obtain component A.

[0055] Furthermore, in step (2), silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane are added to a vacuum planetary mixer in proportion, and stirred for 80 minutes at a vacuum degree of -0.09 Mpa and a rotation speed of 1200 rpm to obtain component B.

[0056] The rest of the content of this embodiment is the same as that of Embodiment 1 and will not be repeated here.

[0057] Example 3 This embodiment provides a low water vapor transmission rate two-component sealant composition, including component A and component B, wherein component A includes the following raw materials in parts by weight: 45 parts of alkoxy-terminated polydimethylsiloxane, 60 parts of nano calcium carbonate, 1 part of vinyl trimethoxysilane, 3 parts of methyl trimethoxysilane, 1 part of bisaminosilane oligomer, and 0.08 parts of organic tin chelate; component B includes the following raw materials in parts by weight: 18 parts of silane-terminated polyether polymer, 32 parts of nano calcium carbonate, 8 parts of maleic anhydride polyisobutylene, 12 parts of polyisobutylene, 4 parts of butyl rubber, and 0.5 parts of vinyl trimethoxysilane. The organic tin chelate is di-n-butyl di(acetylacetonato)tin.

[0058] The rest of the content of this embodiment is the same as that of Embodiment 1 and will not be repeated here.

[0059] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, the preparation method of the silane-terminated polyether polymer comprises the following steps: (S1) under the protection of nitrogen atmosphere, polyoxypropylene glycol and polytetrahydrofuran diol are added into a container, heated to 95° C., 3-isocyanate propyltriethoxysilane and a catalyst are added dropwise while stirring, and reacted for 6 hours to obtain a mixture 1; (S2) Adding nano sodium carbonate to the mixture, stirring at 85° C. for 4 h, degassing under reduced pressure at a vacuum degree of -0.09 MPa, and filtering to obtain a filtrate to obtain a silane-terminated polyether polymer.

[0060] The appearance of the silane-terminated polyether polymers prepared in Example 1 and Comparative Example 3 was observed, and it can be seen that the silane-terminated polyether polymer of Example 1 is a colorless transparent liquid, and the silane-terminated polyether polymer of Comparative Example 1 is a light yellow liquid. The silane-terminated polyether polymers of Example 1 and Comparative Example 3 were placed in a constant temperature drying oven at 80° C. for 8 days, and the surface drying time was measured according to GB / T 13477.5-2002. It can be seen that the silane-terminated polyether polymer of Comparative Example 1 was surface dried and solidified after 2 days, while the properties of the silane-terminated polyether polymer of Example 1 were basically unchanged, and the fluidity was good, there was no skinning and surface drying phenomenon, and it had good storage stability.

[0061] The rest of the contents of this comparative example are the same as those of Example 1 and will not be described again here.

[0062] Comparative Example 2 The difference between this comparative example and Example 1 is that the two-component sealant composition in this comparative example does not contain maleic anhydride polyisobutylene, and is replaced by an equal amount of alkoxy-terminated polydimethylsiloxane. The rest of the contents of this comparative example are the same as those of Example 1 and will not be repeated here.

[0063] Comparative Example 3 The difference between this comparative example and Example 1 is that the two-component sealant composition in this comparative example does not contain bisaminosilane oligomer, but is replaced by an equal amount of silane-terminated polyether polymer. The rest of this comparative example is the same as Example 1 and will not be repeated here.

[0064] Component A and component B in the two-component sealant compositions prepared in Examples 1-3 and Comparative Examples 1-3 were mixed uniformly in a mass ratio of 1:1, and then applied to photovoltaic modules for performance testing. The test results are shown in Table 1 below: project Dry time Water vapor transmission rate g / m2 / 24h, 38℃ Shear strength / Mpa Tensile strength / Mpa Shear strength after thermal cycle test / Mpa Example 1 14 1.6 2.3 2.1 2.1 Example 2 12 2.1 2.5 2.0 2.2 Example 3 17 1.7 2.2 2.3 1.9 Comparative Example 1 10 6.7 1.6 1.9 1.3 Comparative Example 2 15 4.6 2.0 1.4 1.6 Comparative Example 3 18 9.1 1.9 1.8 1.5 Among them, the surface drying time, shear strength (anodized aluminum), tensile strength and thermal cycle performance tests of the two-component sealant composition are tested in accordance with GB / T29595-2013; the water vapor transmission rate is tested in accordance with GB / T 1037-2021.

[0065] In summary, the two-component sealant composition of the present invention has low water vapor permeability and good tensile shear strength, tensile strength and heat cycle resistance. When applied to photovoltaic modules, it can improve the problem of photovoltaic modules affecting luminous efficiency due to water vapor permeation, and help improve the sealing construction efficiency of photovoltaic modules.

[0066] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A two-component sealant composition with low water vapor transmission rate, characterized in that: The invention comprises a component A and a component B. The component A comprises the following raw materials in parts by weight: 30-50 parts of alkoxy-terminated polydimethylsiloxane, 40-70 parts of nano calcium carbonate, 0.5-1 parts of vinyl trimethoxy silane, 1-4 parts of methyl trimethoxy silane, 0.5-1 parts of bisamino silane oligomer and 0.02-0.08 parts of organic tin chelate; the component B comprises the following raw materials in parts by weight: 10-20 parts of silane-terminated polyether polymer, 20-50 parts of nano calcium carbonate, 2-10 parts of maleic anhydride polyisobutylene, 5-15 parts of polyisobutylene, 1-5 parts of butyl rubber and 0.3-0.5 parts of vinyl trimethoxy silane.

2. The low water vapor transmission rate two-component sealant composition according to claim 1, characterized in that: The alkoxy-terminated polydimethylsiloxane is at least one of trimethoxy-terminated polydimethylsiloxane and vinyl dimethoxy-terminated polydimethylsiloxane.

3. The low water vapor transmission rate two-component sealant composition according to claim 1, characterized in that: The molecular weight of the polyisobutylene is 800-2400.

4. The low water vapor transmission rate two-component sealant composition according to claim 1, characterized in that: The preparation method of the silane-terminated polyether polymer comprises the following steps: (S1) under the protection of nitrogen atmosphere, polyoxypropylene glycol and polytetrahydrofuran diol are added into a container, heated to 90-100° C., 3-isocyanate propyltriethoxysilane and a catalyst are added dropwise while stirring, and reacted for 4-7 hours to obtain a mixture 1; (S2) Adding white carbon black to the mixture, stirring at 80-90° C. for 3-5 hours, degassing under reduced pressure, and filtering to obtain a filtrate to obtain a silane-terminated polyether polymer. The low water vapor transmission rate two-component sealant composition according to claim 6, characterized in that: in step (S1), the catalyst is at least one of stannous octoate, dibutyltin dilaurate and dibutyltin diacetate.

5. The low water vapor transmission rate two-component sealant composition according to claim 6, characterized in that: In step (S1), the molecular weight of the polyoxypropylene glycol is 6000-14000.

6. The low water vapor transmission rate two-component sealant composition according to claim 6, characterized in that: In step (S1), the mass ratio of polyoxypropylene glycol to polytetrahydrofuran diol is 2-4:1, and the addition ratio of polyoxypropylene glycol, polytetrahydrofuran diol and 3-isocyanate propyl triethoxy silane is such that the molar ratio of hydroxyl group to isocyanate group is 1:0.9-1.

1.

7. The low water vapor transmission rate two-component sealant composition according to claim 1, characterized in that: The organic tin chelate is at least one of chelated tin U-220H, chelated tin U-303 and chelated tin KRA-1.

8. The low water vapor transmission rate two-component sealant composition according to claim 1, characterized in that: In the components A and B, the particle size of the nano calcium carbonate is 30-80nm.

9. A method for preparing the two-component sealant composition with low water vapor transmission rate according to any one of claims 1 to 9, characterized in that: The steps include: (1) taking alkoxy-terminated polydimethylsiloxane, nano-calcium carbonate, vinyl trimethoxysilane, methyl trimethoxysilane, bisaminosilane oligomer and organic tin chelate in proportion, stirring and mixing them evenly under vacuum conditions to obtain component A; (2) taking silane-terminated polyether polymer, nano-calcium carbonate, maleic anhydride polyisobutylene, polyisobutylene, butyl rubber and vinyl trimethoxysilane in proportion, stirring and mixing them evenly under vacuum conditions to obtain component B; (3) When in use, component A and component B are mixed in proportion to obtain a two-component sealant composition; Among them, steps (1) and (2) can be performed simultaneously or in a reversed order.

Citation Information

Patent Citations

  • Solar energy photovoltaic component seal gum and synthesis method thereof

    CN101735745A

  • Dealcoholized photovoltaic module sealant and preparation method thereof

    CN113337245A